The Development of Career Learning Program with Modeling Technique to Improve Student Career Awareness - Keumala, Elsa; Nurihsan, Juntika; Budiamin, Amin (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2018)
The research is based on the lack of career students awareness in the elementary school. Focus on this research is the development of career guidance program with modeling technique to improve career awareness of student. The purpose of this study is to generate career guidance program with modeling technique to improve student career awareness. Research and development approach conducted through several steps, namely: needs assessment, program planning, implementation of program, evaluation, and follow-up. The data analysis technique was used Paired sample t-test to determine the impact of the program. The participant is the student at the fifth grade Al-Fityan elementary school Aceh in the year 2017/2018 which selected using purposive sampling. The self-developed career awareness instrument designed in the Likert scale with coefficient reliability 0,800. The finding of a research states that main indicator of the successful program evaluation is the improvement of the level of career awareness. This research concludes that the program of the career guidance using the modeling technique is effective to improve the awareness of student career.